Urban Bus Service Quality through Sustainable Assessment Model - Syazwan Baharum; Suria Haron; Iqhlima Ismail; Jezan Md Diah (International Journal of Supply Chain Management, 2019)
This article presents the sustainable assessment of service quality dimensions of urban bus service quality in order to support decision making and policy challenges in term of environment, economic and social context. A multiple-item scale of a sustainability assessment model was conducted on U43 Rapid KL buses to evaluate passengers’ satisfaction based on their travel experience. The data were collected via survey questionnaires from 110 respondents (bus users) who are using the route. Findings indicated 5 significant dominant dimensions for the route, which are Environment, Reliability, Responsiveness, Physical Facilities and Safety. The higher value of Reliability is -1.254 was found to be the critical dimension and showed that the bus is unpunctual. This has lead people to incline more towards the usage of personal transportation. The result helped the researchers to identify the shortcomings of the current service and deliver some recommendations that can improve the service quality to attract new passengers.